2021
DOI: 10.3390/biom11111564
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological and Pathological Role of Tissue Nonspecific Alkaline Phosphatase beyond Mineralization

Abstract: Tissue-nonspecific alkaline phosphatase (TNAP) is a key enzyme responsible for skeletal tissue mineralization. It is involved in the dephosphorylation of various physiological substrates, and has vital physiological functions, including extra-skeletal functions, such as neuronal development, detoxification of lipopolysaccharide (LPS), an anti-inflammatory role, bile pH regulation, and the maintenance of the blood brain barrier (BBB). TNAP is also implicated in ectopic pathological calcification of soft tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 193 publications
(227 reference statements)
0
17
0
Order By: Relevance
“…ALP can detoxify bacterial toxins and pro-inflammatory mediators, e.g., adenosine-tri-phosphate, through the dephosphorylation of various compounds. In some animal models of sepsis, ALP has been shown to improve survival rates by reducing inflammation and organ dysfunction [ 48 , 49 , 50 , 51 ]. Clinical studies of different intravenous ALP compounds in sepsis have produced promising renoprotective results.…”
Section: The Role Of Alp/balp In Inflammation Metabolic Syndrome and ...mentioning
confidence: 99%
“…ALP can detoxify bacterial toxins and pro-inflammatory mediators, e.g., adenosine-tri-phosphate, through the dephosphorylation of various compounds. In some animal models of sepsis, ALP has been shown to improve survival rates by reducing inflammation and organ dysfunction [ 48 , 49 , 50 , 51 ]. Clinical studies of different intravenous ALP compounds in sepsis have produced promising renoprotective results.…”
Section: The Role Of Alp/balp In Inflammation Metabolic Syndrome and ...mentioning
confidence: 99%
“…23,26 Furthermore, TNAP plays a crucial role in neurotransmitter synthesis and spinal cord myelination. 13,14 30 , showed that ALP levels were significantly altered in stroke patients who underwent cardiac bypass surgery as a result of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Under the influence of TNAP, different neurotransmitters are synthesized and regulated. 13,14 In different regions of the world, researchers are investigating the levels of ALP and specific TNAP in brain tissues, cerebrospinal fluid samples, and blood samples to determine different variations in TNAP levels in animal and human models. In the brain, ALP is also involved in phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…ALP, a type of metalloenzyme, requires Zn 2+ and Mg 2+ to coordinate with specific amino acid residues. It shows anti-inflammatory activity partly by mediating the detoxification of lipopolysaccharide (LPS) through dephosphorylation (1,52) . ACP also targets the phosphate bonds of external entities for conducting hydrolysis and advance their degradation (51,53) .…”
Section: Accepted Manuscriptmentioning
confidence: 99%